2018
DOI: 10.1089/jpm.2017.0043
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Needs in an Acute Internal Medicine Ward in Mexico

Abstract: The number of patients requiring palliative care in internal medicine wards may be excessive to the current palliative care structures available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Proportions of patients with PC needs vary (9-73%), and people are often identified late in their disease trajectory, which bears important consequences for care [9][10][11][12][13][14][15][16][17][18]. These consequences include, but are not limited to (i) excess hospital mortality, whereby 80% of palliative patients die in hospital when the majority of people wish to die at home [19,20]; (ii) suboptimal symptom management [21][22][23]; (iii) unplanned hospitalisations with long hospital stays [24,25]; (iv) prescription of inappropriate treatments due to a lack of advance care planning [26,27]; and, (v) insufficient support for the patient and their relatives [24,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Proportions of patients with PC needs vary (9-73%), and people are often identified late in their disease trajectory, which bears important consequences for care [9][10][11][12][13][14][15][16][17][18]. These consequences include, but are not limited to (i) excess hospital mortality, whereby 80% of palliative patients die in hospital when the majority of people wish to die at home [19,20]; (ii) suboptimal symptom management [21][22][23]; (iii) unplanned hospitalisations with long hospital stays [24,25]; (iv) prescription of inappropriate treatments due to a lack of advance care planning [26,27]; and, (v) insufficient support for the patient and their relatives [24,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of patients in need of PC varies from 9% to 73% in various acute care settings, with the highest prevalence occurring in clinical settings, such as internal medicine or oncology (5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence varies from 9% to 73% in acute care settings depending on pathologies, co-morbidities or frailty. [1][2][3][4][5] An international prevalence study revealed that the proportion of individuals who died from diseases indicating a need for palliative care ranged from 38% to 74%. 6 According to Murtagh et al, 7 63% to 82% of the population will need palliative care at some point of their disease trajectory.…”
Section: Introductionmentioning
confidence: 99%